Natural History in Mexican Trades Magazines, 1840-1855 - Vega y Ortega, Rodrigo (Revista Complutense de Historia de América, 2012)
The educational aspect of Natural History, as a scientific discipline, occupied an important place in various Mexican magazines intended for artisan groups, published in the years 1840-1855. The scientific articles in these magazines were one of the available resources for these readers to educate themselves informally in sciences which could be applied to their work, such as Botany, Zoology and Mineralogy. The reading of the naturalists’ works had, among its aims, a rational and pragmatic use of the natural resources of the country for artisans’ needs. The study period covers the years before the founding of the Escuela de Artes y Oficios (1856) in Mexico City. The articles in these trades magazines had an impact on this educational institution, as the scientific and technical subjects needed by young students from the craftsmen’s guilds of the various regions of the republic, were taught formally for the first time.
Keywords: Natural History; Artisans; Magazines; History of Science; Mexico; 19th-Century.